Potential Effects of Dietary Isoflavones on Drug-Induced Liver Injury - Liangliang Yao; Muhammad Farrukh Nisar; Tingdong Yan; Chunpeng (Craig) Wan (Journal of Food Quality)
Numerous prescribed drugs and herbal and dietary supplements have been reported to cause drug-induced acute liver injury, which is a frequent cause of acute liver failure (ALF). It is a tremendous challenge with ever-increasing drug application in the medication system for huge populations. Drug-induced acute liver injury can lead to diverse pathologies similar to acute and chronic hepatitis, acute liver failure, biliary obstruction, fatty liver disease, and so on. Recently, extensive work demonstrated that isoflavones play an essential and protecting role in drug-induced liver injury (DILI). The isoflavones mediated hepatoprotection by modulating specific genes linked with control of cellular redox homeostasis and inflammatory responses. Isoflavones upregulate oxidative stress-responsive nuclear factor erythroid 2-like 2 (Nrf2), downregulate inflammatory nuclear factor-κB (NF-κB) signaling pathways, and modulate a balance between cell survival and death. Moreover, isoflavones actively inhibit the expression of cytochromes P450 (CYPs) enzyme during drug metabolism. Moreover, isoflavones are also linked with farnesoid X receptor (FXR) activation and signal transducer and activator of transcription factor 3 (STAT3) phosphorylation in hepatoprotection DILI. In vivo and in vitro studies clearly stated that isoflavones bear strong antioxidant potential and promising agents for hepatotoxicity prevention and stressed their potential role as therapeutic supplements in DILI. The current review will elaborate on isoflavones’ preventive and therapeutic potential concisely and highlight various molecular targets to exert a protective effect on DILI.